Respuesta del pimiento capsicum annuum l. a la aplicación de bioestimulantes en la parroquia El Progreso cantón Pasaje - Armijos Encalada, Stalin Iván (2014)
This investigation consisted in assessing the effects of different bio-stimulants over the physiology and yield of green peppers (Capsicum annuum L.). The work was carried out in El Progreso, located in the city of Pasaje, Provincia de El Oro. The biostimulants used for this investigation were: Evergreen, Bio-energía, FertiEstim, Agrostemin, Cytokin; which were compared to each other and a control treatment; the biostimulants were applied thrice in the plantation. The number of plants used in this study was 700, which were divided into 24 experimental plots using a randomized block design. The variables taken were: plant height at 30, 60 and 90 days after transplantation, number of fruits per plant, weight, length and diameter of fruits and yield. In the ANOVA for the variable height at 30 days, significance was determined for values of F at 0.01, being the product Cytokin the one who had the highest mean with 11.1 cm, however, for the variables height at 60 and 90 days there was no significance. In the same analysis for the variable number of fruits significance at values of F 0.05% was determined, obtaining Evergreen the highest average among the biostimulants. For variables weight, length and diameter of fruits there were no statistical differences. Regarding yield (Tm per hectare), better results were obtained with the product Cytokin, sporting a mean of 11.17 Tm / ha. After completing these statistical analyzes I proceeded to calculate the production costs for each treatment, and with the use of several formulas it was determined that all treatments, including the control treatment are profitable, earning the highest return, 54.16% using the product Cytokin.